Association between changes in habitual stepping activity and cognition in older adults - Myles W. O’Brien; Nick W. Bray; Isadora Quirion; Shirko Ahmadi; Pierre Faivre; Francois Gallant; Caroline Gagnon; Martin Sénéchal; Olivier Dupuy; Mathieu Bélanger; Said Mekari (Scientific Reports, 2024)
Abstract Advancing age is associated with declines in cognitive function. Although physical activity is thought to protect against this decline, it is unclear how a short-term uptake in daily steps or a decline in day-to-day step variability may contribute to cognition among older adults. We tested associations between changes in step counts, day-to-day step variability and executive cognitive functions among older adults taking part in a physical activity intervention. Thirty-seven older adults (33 females; 71.4 ± 6.3 years) completed a 10-week personalized physical activity intervention. Participants wore a Fitbit to measure daily step counts throughout the study. They also completed a computerized Stroop task before and after the intervention. Average step counts and step count variability via average-real-variability (ARV) were determined. Compared to pre-intervention, step counts increased (p < 0.001) and step variability decreased post-intervention (p = 0.04). Models describing the changes in step counts and ARV over the 10-weeks were cubic (both, p < 0.04). Reaction times during the simple (p = 0.002) and switching (p = 0.04) conditions were faster post-intervention. Change in step variability was positively associated with the change in reaction time for the switching condition (β = 0.029, p = 0.002). On average, a reduction in day-to-day step variability was associated with improvements in cognitive flexibility.